2019
DOI: 10.1177/0162643419890249
|View full text |Cite
|
Sign up to set email alerts
|

Video Prompting to Teach Robotics and Coding to Middle School Students With Autism Spectrum Disorder

Abstract: Video-based modeling is an evidence-based practice for teaching social and communication skills, functional and daily living skills, and some academic skills (i.e., math) to students with autism spectrum disorder. The efficacy of video-based modeling, however, has not yet been established for STEM skills related to science, technology, or engineering. Drawing on findings from a systematic review of video-based modeling to teach academic skills to students with autism spectrum disorder and/or intellectual disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In recent years, technology has played an increasingly important role in assisting teachers with the instruction of science subjects, especially for students with disabilities (McKissick et al, 2018;Turan & Atila, 2021;Wright et al, 2021). Numerous studies have demonstrated the various applications of technology in this context, including serving as a direct instructional instrument (Gavronskaya et al, 2021) and facilitating the creation of interactive educational materials (Mallidis-Malessas et al, 2022;Ok et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, technology has played an increasingly important role in assisting teachers with the instruction of science subjects, especially for students with disabilities (McKissick et al, 2018;Turan & Atila, 2021;Wright et al, 2021). Numerous studies have demonstrated the various applications of technology in this context, including serving as a direct instructional instrument (Gavronskaya et al, 2021) and facilitating the creation of interactive educational materials (Mallidis-Malessas et al, 2022;Ok et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies (e.g., Elshahawy et al, 2020;Knight et al, 2019a;Wright et al, 2019) referred to certain requirements the students had to fulfill to be included in the sample (e.g., sufficient motor, cognitive and communication skills). As students with ASD (and ADHD) do not form a homogeneous group but show various manifestations of the disorder, such findings are not generalizable to all students with ASD and/or ADHD.…”
Section: Samplementioning
confidence: 99%
“…As CT is applicable to various aspects of daily life (Tsortanidou et al, 2021) this finding is considered particularly valuable. Furthermore, some follow-up studies (Knight et al, 2019a, b;Sakka et al, 2018;Wright et al, 2019) revealed that students were able to maintain the skills acquired.…”
Section: Fostering Programming Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides those traditionally linked to technology, robotic platforms have also proved effective for interdisciplinary knowledge learning and improving different skills, such as; creativity, collaboration, communication, or autonomy [12]. Thus, on the one hand, they are beneficial for students studying different stages of the educational process, and on the other hand, for students with specific needs for educational support [29], [27].…”
Section: B Robots As Ict Toolsmentioning
confidence: 99%